SISTEM PENDUKUNG KEPUTUSAN PENJURUSAN SISWA PADA SMA PANCAMARGA 1 LAMONGAN MENGGUNAKAN METODE FUZZY - Ahmad Fathoni; Mustain Mustain; Retno Wardhani (Joutica, 2018)
must know what factors affect the performance of teachers. The results of the analysis will be beneficial to make the education development program optimally and it is very necessary to advance the quality of education. Students need special attention from the government and society therefore the government regulates the improvement of the quality of teachers or teachers nationally through Law No. 20 of 2003 on National education system. In order to enforce the law, the government issued Regulation No. 19 of 2004 on the National Education standard. Therefore developed sebi student decision support system on the sma pancamarga 1 Lamongan using fuzzy.